2018
DOI: 10.1111/eje.12338
|View full text |Cite
|
Sign up to set email alerts
|

A rapid review of serious games: From healthcare education to dental education

Abstract: Serious games provide an option for healthcare and dental education but remain underutilised and researched. At best, they offer a similar experience to other methods in relation to educational outcome; however, they can provide a supplementary strategy to engage students and improve learner satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
54
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 38 publications
4
54
0
4
Order By: Relevance
“…The review of learning efficacy showed that serious games for health professions education are efficacious for short-term learning. The finding is consistent with studies by Sipiyaruk 48 and Connolly 49 . The former described the teaching of medicine and dentistry using serious games, and the latter was a review of the use and impact of computer and serious games in a broader context.…”
Section: Discussionsupporting
confidence: 93%
“…The review of learning efficacy showed that serious games for health professions education are efficacious for short-term learning. The finding is consistent with studies by Sipiyaruk 48 and Connolly 49 . The former described the teaching of medicine and dentistry using serious games, and the latter was a review of the use and impact of computer and serious games in a broader context.…”
Section: Discussionsupporting
confidence: 93%
“…Level 1 (reaction) was assessed thought questionnaires by 6 of the 7 included studies. Our results show a positive attitude related to TEL application in periodontics education, which was also emphasized by other studies in dental education 2,42‐44 . This finding might suggest that TEL implementation in undergraduate dental courses motivate students through their learning process.…”
Section: Discussionsupporting
confidence: 86%
“…Our results show a positive attitude related to TEL application in periodontics education, which was also emphasized by other studies in dental education. 2,[42][43][44] This finding might suggest that TEL implementation in undergraduate dental courses motivate students through their learning process. The application of a questionnaire to assess students' attitudes was highlighted by Shoaib et al as an essential tool in evaluating impacts on educational outcomes, especially in a leaner-center approach.…”
Section: Discussionmentioning
confidence: 88%
“…Les résultats élevés de satisfaction montrent un certain engouement des participants pour ce mode pédagogique. Il est reconnu par plusieurs auteurs que, si les jeux sérieux dans le milieu médical offrent des résultats similaires à d'autres méthodes [19], ils peuvent fournir un soutien supplémentaire pour engager les participants et améliorer leur satisfaction [20]. L'intégration du dispositif de formation par simulation au sein de programmes de formation optimise l'impact sur le transfert des connaissances et ainsi la prévention des erreurs médicales.…”
Section: Discussionunclassified